2009
DOI: 10.1007/s12303-009-0022-4
|View full text |Cite
|
Sign up to set email alerts
|

Middle Jurassic tectono-magmatic evolution in the southwestern margin of the Gyeonggi Massif, South Korea

Abstract: Sensitive high-resolution ion microprobe (SHRIMP) U-Pb zircon dates and geochemical and isotopic (Sr and Nd) data were obtained for Middle Jurassic granitoids from the Buyeo area along the southwestern margin of the Gyeonggi Massif, South Korea. Foliated 179 Ma granitoids are dominated by granite and diorite, non-foliated 167 Ma granitoids include granite to alkalifeldspar granite, and the youngest, non-foliated 165 Ma granitoids consist of alkali-feldspar granite. The 179 Ma and 167 Ma rocks are geochemically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 33 publications
0
12
0
1
Order By: Relevance
“…Cluzel et al (1991) suggested that the shear zones are amalgamated during the Triassic associated with the Chinese continental collision. However, as mentioned before, geochronologic data for the shearing indicate that the Honam shear zone dominantly initiated during the Middle to Late Jurassic and then reactivated during the Early Cretaceous (Cho et al, 1999;Cheong et al, 2006;Kim et al, 2009;Park et al, 2009).…”
Section: Timing Of Mylonitization Of Granitoids In the Taebaeksan Basmentioning
confidence: 64%
See 2 more Smart Citations
“…Cluzel et al (1991) suggested that the shear zones are amalgamated during the Triassic associated with the Chinese continental collision. However, as mentioned before, geochronologic data for the shearing indicate that the Honam shear zone dominantly initiated during the Middle to Late Jurassic and then reactivated during the Early Cretaceous (Cho et al, 1999;Cheong et al, 2006;Kim et al, 2009;Park et al, 2009).…”
Section: Timing Of Mylonitization Of Granitoids In the Taebaeksan Basmentioning
confidence: 64%
“…1a) is recognized by mylonitized granitoid rocks. The Honamshear zone mainly developed around the tectonic boundaries between the Yeongnam massif and the Okcheon Basin (e.g., Sunchang, Cheongsan, and Yecheon shear zones; Cho et al, 1999;Cheong et al, 2006;Cho et al, 2007) and within the Okcheon Basin (Jeonju-Muan shear zones; Lee et al, 2001;Lee et al, 2003;Kim et al, 2003;Park et al, 2009). These shear zones are dominantly characterized by right lateral strike-slip movement of ductile or brittle-ductile shearing (Kim and Kee, 1994;Lee, 1996a, 1996b;Chough et al, 2000;Ree et al, 2001).…”
Section: Timing Of Mylonitization Of Granitoids In the Taebaeksan Basmentioning
confidence: 99%
See 1 more Smart Citation
“…(g) Koh et al, 1996Kim, et al, 2005;Kim et al, 2009;Kim et al, 1995;Kim and Park, 1996;Kim et al, 1997;Min and Kim, 1996;Park et al, 1997;Wee et al, 2007;Wee and Kim, 2009;Wee et al, 2005;Wee et al, 2006;Youn and Park, 1995;Yun andHong, 2004, Yun et al, 2006;Lee et al, 2008;Cheong et al, 1998;Jwa et al, 1998;Yun, 2003. (h) Min andKim, 1996;Park, 2009;Park et al, 1997;Lee et al, 2008. (i) Lee et al, 1997a.…”
mentioning
confidence: 99%
“…The authors further suggest that the Busan complex is possibly linked with the Hida-Oki terrane in Japan. Park et al (2009) report the SHRIMP U-Pb zircon ages, together with geochemical and Sr-Nd isotopic data, for Jurassic granitoids from the southwestern Gyeonggi massif, Korea. Foliated and non-foliated I-type granitoids are dated at ca.…”
mentioning
confidence: 99%